Penggunaan Media Search Engine dalam Meningkatkan Civic Intelligence Siswa pada Mata Pelajaran PKN: Studi Deskriptif Siswa Kelas VII di SMP Islam Fathia Kota Sukabumi - Tina Septiana; Heri Ginanjar (Indra institute Research & Publication, 2023)
This study aims to explore the benefits of using search engine media in improving students' civic intelligence in Civic Education (Civics). Media search engines, such as online search engines, provide easy and quick access to various sources of information relevant to Civics Education materials. This study involved high school student participants who were involved in the use of search engines as a learning tool in Civics class. The results showed that the use of search engines has significant benefits in improving students' civic intelligence. The students reported that they were able to access extensive and diverse information, deepen their understanding of Civics concepts, and develop digital literacy skills. The use of search engines also provided opportunities for students to actively participate in class discussions, presentations and Civics projects.